From sun up [videorecording] - M'mbugu, Flora (Maryknoll, N.Y. Maryknoll World Video Library)
This is story of women of black Africa, of their strength and courage of their daily struggle, concerns and challenges "From sun up" is a candid, authentic picture of the dawn-to-dusk, life-giving, life-sustaining effort of these women to survive and prosper. It reflects the condition of women everywhere, especially those of the Third World. Finally, it dramatically illustrates that the source of her hope and her sense of the future lies in women's support of each other.
DVD
Keywords: Feature films